SENGKETA KEWENANGAN ANTARA KANTOR STAF PRESIDEN DENGAN WAKIL PRESIDEN DAN KEMENTERIAN KOORDINATOR NEGARA - Ni Luh Putri Santika (University of Udayana, 2016)
This paper entitled “Authority Dispute Between The Office of Presidential Staff with the Vice President and also Minister of State Coordinator”. This paper uses normative analytical method with the statute approach and case approach. The Office of Presidential Staff is a new institution that born through Presidential Decree No. 26 of 2015. The chief of Presidential Staff was given authority by This Presidentian Decree to take control of the program priorities. It means that The Office of Presidential Staff have authority to make any programs and also do controlling and evaluating the ministers as routinely. Certainly this could potentially lead to dispute the authority with the Vice President and also Minister of State Coordinator. Presidential Staff’s authority can not be bigger than Vice President, Minister of State Coordinator and also the ministers of state, because the authority expansion of the chief of Presidential Staff would reduce the authority of the Vice President and also Minister of State Coordinator. Establishment of the Office of Presidential Staff is the prerogative of the president in accordance with The 1945 Constitution of the Republic of Indonesia but the authority which is granted to The Office of Presidential Staff is not in accordance with the constitution and legislation, especially in the law concerning the state ministries and the law concerning the Formation of Law and Regulations. President should reassess the institutional functions of Presidential aide. The burden and responsibility of government should be enclosed by the Cabinet and ministry-level agencies.Makalah ini berjudul